Mechanical efficiency during different submaximal exercise intensities - Pavlova, E. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of this study was to examine mechanical efficiency changes during submaximal exercises above anaerobic threshold and during standard steady-rate test applied as a pre-and post-test after exhaustive cycle ergometer load (rowers and cyclists).